Factors associated with depressive state in patients with myasthenia gravis: a multicentre cross-sectional study. Issue 2 (19th December 2011) - Suzuki, Yasushi; Utsugisawa, Kimiaki; Suzuki, Shigeaki; Nagane, Yuriko; Masuda, Masayuki; Kabasawa, Chiaki; Shimizu, Yuko; Utsumi, Hiroya; Uchiyama, Shinichiro; Fujihara, Kazuo; Suzuki, Norihiro
Abstract : Objectives: The objective of this study was to examine clinical factors associated with depressive state in patients with myasthenia gravis (MG). Design: Cross-sectional study. Setting and participants: We evaluated 287 consecutive cases of MG seen at six neurological centres located in Eastern Japan. Outcome measures: All MG patients completed the Japanese version of the Beck Depression Inventory–Second Edition (BDI-II). Disease severity was determined according to the MG Foundation of America (MGFA) quantitative MG score, MG activities of daily living scale and MG composite scale (MG composite). Clinical state following treatment was categorised according to MGFA postintervention status. Associations between detailed clinical parameters of MG and BDI-II score were then examined statistically. Results: Mean BDI-II score for patients with MG (11.0±8.1) did not differ substantially from and overlapped with that reported as the Japanese standard (8.7±6.4). The mean +2 SDs for the Japanese standard is 21.5, approximately equal to the cut-off level indicative of moderate or worse depression (>20 points) in the original English version. We thus defined BDI-II >21.5 as depressive state, with a frequency of 13.6% in patients with MG. Multivariate logistic regression analysis revealed current dose of oral prednisolone (OR 1.09, 95% CI 1.02 to 1.17; p=0.01), unchanged MGFA postintervention status (OR 3.55, 95% CI 1.18 to 10.71; p=0.02), time since onset (OR 0.93, 95% CI 0.87 to 0.99; p=0.03) and MG composite (OR 1.16, 95% CI 1.00 to 1.34; p=0.046) as factors independently associated with depressive state in MG. Conclusions: Dose of oral corticosteroids appears to represent the major factor associated with depressive state in MG. Unchanged status despite treatment and early disease stage are also significant background factors for depressive state, along with disease severity.